The role of ICT in Moroccan smart cities: towards innovative hospital logistics - Nissrine Khouna; Kaoutar Hablatou; Mostapha Amri (Smart Cities and Regional Development Journal)
This article explores the role of information and communication technologies (ICT) in the development of smart cities in Morocco, with a particular focus on hospital logistics. It aims to demonstrate how the integration of ICT can transform logistics practices, improve the efficiency of hospital operations and address sustainability challenges in a rapidly evolving urban context. This theme is essential to support Morocco's efforts to modernize healthcare infrastructures and make the digital transition. The study draws on existing research on the impact of ICT in hospital logistics systems and on international smart city initiatives, while integrating analyses of specific examples in Morocco. It follows on from published work on the synergies between digitalization and public service performance. A qualitative methodology was adopted, combining documentary analysis and case studies of Moroccan smart city projects. Interviews with healthcare and logistics professionals provided practical perspectives on the challenges and opportunities associated with the use of ICT. The results reveal that integrating ICT into smart city hospitals enables better management of logistics flows, optimization of resources and enhanced coordination between players. These improvements contribute not only to the efficiency of care, but also to the resilience of hospital systems in the face of growing urban constraints. This study offers concrete guidelines for decision-makers and practitioners, highlighting the need for appropriate digitization policies. It also offers innovative thinking on the intersection between hospital logistics and intelligent urbanization, making a valuable contribution to research and practice in this field.